2019
DOI: 10.1021/acs.langmuir.9b02459
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High Performance of Hyper-Crosslinked Phosphate-Based Polymer for Uranium and Rare Earth Element Adsorption in Aqueous Solution

Abstract: In this work, a new type of hyper-crosslinked phosphate-based polymer (HCPP) polymerized by bis­(2-methacryloxyethyl)­phosphate has been developed for uranium and rare earth element (REE) extraction in an aqueous solution. The influence of the pH value, contact time, initial concentration, temperature, and competing ions on uranium adsorption of HCPP is investigated in detail. HCPP exhibits a maximum uranium adsorption capacity of up to 800 mg g–1 at pH = 6.0 and excellent selectivity toward uranium adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…The removal rate of Tb(III) by spores showed a more obvious change, increasing rapidly with the increase in pH. It is likely that, with the increase in the pH value, functional groups such as phosphates on the spore surface are deprotonated, cations are reduced, and negative charges are increased; meanwhile, rare earth ions still exist in the form of positive electricity, enhancing the electrostatic interaction and complexation between spores and rare earth ions, and increasing the removal rate of Tb(III) [26,27]. When the pH was 7.5, the percentage of Tb(III) removed by the spores reached equilibrium.…”
Section: Effects Of Adsorption Conditions On Tb(iii) Adsorptionmentioning
confidence: 99%
“…The removal rate of Tb(III) by spores showed a more obvious change, increasing rapidly with the increase in pH. It is likely that, with the increase in the pH value, functional groups such as phosphates on the spore surface are deprotonated, cations are reduced, and negative charges are increased; meanwhile, rare earth ions still exist in the form of positive electricity, enhancing the electrostatic interaction and complexation between spores and rare earth ions, and increasing the removal rate of Tb(III) [26,27]. When the pH was 7.5, the percentage of Tb(III) removed by the spores reached equilibrium.…”
Section: Effects Of Adsorption Conditions On Tb(iii) Adsorptionmentioning
confidence: 99%
“…Hyper-cross-linked porous polymers (HCPs) are POPs that have been studied in various research areas such as gas adsorption, water treatment, and organic catalysts. They provide a good choice for studying the effect of heteroatoms in the iodine capture process because such materials can be synthesized by a simple knitting method.…”
Section: Introductionmentioning
confidence: 99%
“…2−4 Previous studies have shown that the discharge of uranium and its compounds into the water environment causes immense damage to the ecological environment. 5,6 Moreover, if uranium enters the body, it deposits into the lungs and travels through the bloodstream to the kidneys. This causes irreversible damage to the human body and kidneys within a short period and even causes death.…”
Section: ■ Introductionmentioning
confidence: 99%